Do geriatric healthcare teams work?. (December 2011) - Kane, Robert L; Shamliyan, Tatyana A; McCarthy, Teresa
There is great enthusiasm for healthcare teams. Teams are viewed as central in modern chronic disease management strategies. However, the evidence does not support the excitement. Our systematic review of randomized controlled trials of team care found little consistency in what constitutes a healthcare team. Few have invested in the level of training and maintenance team enthusiasts champion. The evidence of benefit is mixed. Benefits were more likely achieved in the process of care than in improving outcomes. Understanding the benefits of team care requires distinguishing the effects of team care from those of more systematic care, that is, what is done versus who does it. The quality of the research is weak.